2021
DOI: 10.26434/chemrxiv.13618988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Key Role of the Latent N-H Group in Milstein's Catalyst for Ester Hydrogenation

Abstract: <p>We previously demonstrated that Milstein’s seminal diethylamino-substituted PNN-pincer-ruthenium catalyst for ester hydrogenation is activated by dehydroalkylation of the pincer ligand, releasing ethane and eventually forming an NHEt-substituted derivative that we proposed is the active catalyst. In this paper, we present a computational and experimental mechanistic study supporting this hypothesis. Our DFT analysis shows that the minimum-energy pathways for hydrogen activation, ester hydrogenolysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The results from the current study and our earlier two papers, as well as those by others, 21,33 show that ADC is a versatile reaction that may proceed by several different pathways depending on the complex, or can be completely shut down by a rather trivial ligand modification. In this regard, the presence of acetate complexes formed in super dry ethanol (Supelco, max 1 ppm H2O), where the maximum water amount present would have been several times less than the amount of excess base, shows that a Guerbet reaction is an important consideration for catalyst deactivation.…”
Section: Summary Of Reactivity and Catalysissupporting
confidence: 81%
“…The results from the current study and our earlier two papers, as well as those by others, 21,33 show that ADC is a versatile reaction that may proceed by several different pathways depending on the complex, or can be completely shut down by a rather trivial ligand modification. In this regard, the presence of acetate complexes formed in super dry ethanol (Supelco, max 1 ppm H2O), where the maximum water amount present would have been several times less than the amount of excess base, shows that a Guerbet reaction is an important consideration for catalyst deactivation.…”
Section: Summary Of Reactivity and Catalysissupporting
confidence: 81%
“…Several ruthenium and manganese pincer complexes were screened for the amide synthesis under Et 2 O reflux (boiling point 34.6 °C) in the presence of catalytic amounts of t -BuOK. Interestingly, among these complexes, Ru–PNNH complexes 11 1 and 2 , featuring a terminal N–H moiety, displayed catalytic activities toward amide formation even at this low temperature (entries 1–2). Ru–PNNH complexes 1–3 are capable of two distinct modes of metal–ligand cooperation (MLC), amido–amine and aromatization–dearomatization, 11 unlike complexes 4–6 , where only aromatization–dearomatization is possible.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, among these complexes, Ru–PNNH complexes 11 1 and 2 , featuring a terminal N–H moiety, displayed catalytic activities toward amide formation even at this low temperature (entries 1–2). Ru–PNNH complexes 1–3 are capable of two distinct modes of metal–ligand cooperation (MLC), amido–amine and aromatization–dearomatization, 11 unlike complexes 4–6 , where only aromatization–dearomatization is possible. Ru–P Ph NNH complex 3 , with electron-withdrawing Ph substituents on the P donor atom, did not show catalytic activity at this temperature (entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comprehensive experimental and computational study, we demonstrated that RuPNN HEt is a key on-cycle catalytic intermediate, and that the nascent N-H group is intimately involved in both hydrogen activation and the transfer of hydrogen to the substrate. 12 Scheme 1. Conversion of Milstein's Catalyst RuPNN dearom to the form active for ester hydrogenation.…”
Section: Introductionmentioning
confidence: 99%